2017
DOI: 10.36408/mhjcm.v2i3.196
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Diet Modifikasi terhadap Status Gizi Pasien Kanker dengan Kemoradiasi

Abstract: Latar belakang : Pasien kanker stadium lanjut pada umumnya mengalami kurang gizi, karena terjadinya hipermetabolisme dan pengaruh terapi kemoradiasi. Diet modifikasi dengan porsi kecil dan mengandung sumber peptida, BCAA, omega3 dan MCT diharapkan bisa mencegah penurunan berat badan, mengurangi anoreksia dan inflamasi. Tujuan penelitian menganalisis pengaruh pemberian diet modifikasi terhadap kenaikan status gizi pasien kanker. Metode : Rancangan penelitian adalah Randomised Control Trial dengan pre post-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study showed that after receiving a Standardized NCP, the intake of energy and protein inpatients at Dr. Hasan Sadikin General Hospital Bandung had increased significantly and it was positively related [17]. Research by Purwaningsih et al [18] showed that dietary modification in cancer patients has an effect on decreasing anorexia and increasing food intake in cancer patients with chemoradiation therapy in the inpatient room of RSUP Dr. Kariadi and there was a significantly increase in body weight and nutritional status (BMI). This study not in line with Purwaningsih's research.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that after receiving a Standardized NCP, the intake of energy and protein inpatients at Dr. Hasan Sadikin General Hospital Bandung had increased significantly and it was positively related [17]. Research by Purwaningsih et al [18] showed that dietary modification in cancer patients has an effect on decreasing anorexia and increasing food intake in cancer patients with chemoradiation therapy in the inpatient room of RSUP Dr. Kariadi and there was a significantly increase in body weight and nutritional status (BMI). This study not in line with Purwaningsih's research.…”
Section: Discussionmentioning
confidence: 99%